Meeting the Challenges of Chemical and Biological Weapons: Strengthening the Chemical and Biological Disarmament and Non-proliferation Regimes - Edwards, Brett; Novossiolova, Tatyana; Crowley, Michael; Whitby, Simon; Dando, Malcolm; Shang, Lijun (Frontiers in Political Science, 2022)
In this report, we identify some of the key technical and political challenges currently facing the broader Chemical and Biological Weapon (CBW) regime- with a particular emphasis on major forthcoming diplomatic meetings. Most significantly the Ninth Review Conference of the Biological and Toxins Weapons Convention (1972) (BTWC) which will take place in 2022 and preparations for the Fifth Review Conference of the Chemical Weapons Convention (1993) (CWC), expected in 2023. This report is an output of an ongoing project, designed to stimulate thinking and discussion about these issues, within relevant stakeholder communities. The report provides an introduction to this issue area for the general reader before surveying key issues and developing a series of practical policy suggestions for further consideration.